2020
DOI: 10.3389/fnbeh.2020.00074
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and the Role of Estradiol in Mesolimbic Reward Circuits and Vulnerability to Cocaine and Opiate Addiction

Abstract: Although both men and women become addicted to drugs of abuse, women transition to addiction faster, experience greater difficulties remaining abstinent, and relapse more often than men. In both humans and rodents, hormonal cycles are associated with females' faster progression to addiction. Higher concentrations and fluctuating levels of ovarian hormones in females modulate the mesolimbic reward system and influence reward-directed behavior. For example, in female rodents, estradiol (E2) influences dopamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 326 publications
(421 reference statements)
4
48
0
1
Order By: Relevance
“…During abstinence, females experience stronger drug cravings ( 74 ). This is mainly due to the ovarian hormone cycle in females, and short-term exposure to estradiol will increase drug availability ( 75 ). Animal studies further indicate that estradiol may be necessary for the development of substance use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…During abstinence, females experience stronger drug cravings ( 74 ). This is mainly due to the ovarian hormone cycle in females, and short-term exposure to estradiol will increase drug availability ( 75 ). Animal studies further indicate that estradiol may be necessary for the development of substance use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent revision [ 35 ], estradiol level fluctuations are associated with sex differences in dopamine signaling in the mesolimbic reward system; in animal models, it has been demonstrated that striatal dopamine release is increased during phases of the cycle with high levels of estradiol [ 36 ]. Also, high levels of estradiol are related to increased responses to cocaine and cocaine-related cues [ 37 ].…”
Section: Ethiopathogenic Mechanismsmentioning
confidence: 99%
“…This is relevant since women when compared to men transition faster from occasional to compulsive cocaine intake and those with cocaine use disorder experience more cravings, withdrawal symptoms, and worse outcomes (Griffin et al, 1989;Robbins et al, 1999;Van Etten and Anthony, 2001;Becker and Koob, 2016). Similarly, studies in laboratories animals have reported significant sex differences in the locomotor and rewarding effects of cocaine (Kokane and Perrotti, 2020).…”
Section: Introductionmentioning
confidence: 99%